Growing up in America : the power of race in the lives of teens - Christerson, Brad.; Edwards, Korie L.; Flory, Richard W. (Stanford, Calif. : Stanford University Press, 2010)
People's experiences of racial inequality in adulthood are well documented, but less attention is given to the racial inequalities that children and adolescents face. This book provides a first hand account of the different social worlds that teens of diverse racial and ethnic backgrounds experience. In their own words, these American teens describe, conflicts with parents, pressures from other teens, school experiences, and religious beliefs that drive their various understandings of the world. As the book reveals, teens' unequal experiences have a significant impact on their adult lives and their potential for social mobility. Directly confronting the constellation of advantages and disadvantages white, black, Hispanic, and Asian teens face today, this work provides a framework for understanding the relationship between socialization in adolescence and social inequality in adulthood. By uncovering the role racial and ethnic differences play early on, we can better understand the sources of inequality in American life.
Family: learning authority, autonomy, and responsibility -- Peers: influencing attitudes, social acceptance, and personal relationships -- School: motivating achievement, aspirations, and opportunity -- Religion: developing beliefs, experiences, and practices -- Appendix A: Methodology -- Appendix B: Frequencies of racial/ethnic groups -- Appendix C: Regression analyses of NSYR survey data.
Includes bibliographical references (pages 182-195) and index.
Keywords: Teenagers -- United States -- Social conditions; Teenagers -- United States -- Attitudes; Race -- Social aspects -- United States; Socialization -- United States